Legal Position of the Insurance Party in the Execution of Lienage Rights with Subrogation Rights - Rosah Bustami, Rendy (Jurnal Konstatering, 2025)
This study aims to determine and analyzeThe legal position of the insurance party in terms of submitting the execution of mortgage rights which originally held the mortgage rights as a bank as a creditor and the execution of the mortgage rights carried out by the insurance party using the right of subrogation and to analyze the example of the Deed of Granting of Mortgage Rights. This study uses a sociological juridical approach method that uses secondary data as the initial data then continued with primary data in the field or in the community. The research specifications used in this study are descriptive analysis. Based on the research that has been done, it can be concluded that the insurance party has the same legal standing as the bank as a creditor of the Mortgage Right holder so that the execution of the Mortgage Right can be carried out directly by the insurance party with the right of subrogation. In addition, if the insurance party will execute the mortgage rights with the right of subrogation, it can first submit a change in the name of the Mortgage Right holder to the National Land Agency.